Odpowiedzi

2010-03-10T15:02:42+01:00
A)
2(x+1)=4
2x+2=4
2x=4-2
2x=2/2
x=1
b)
4=2(x-1)
4=2x-2
-2x=-2-4
-2x=-6/:(-2)
x=3
c)
3(x-2)=x
3x-6=x
3x-x=6
2x=6/:2
x=3
d)
3(2x+3)=x-1
6x+9=x-1
6x-x=-1-9
5x=8 /5
x=8/5
x=1 i 3/5
e)
4(x-1)=3(x+1)
4x-4=3x+3
4x-3x=3+4
7x=7 /7
x=1
f)
-(x-1)=2
-x+1=2
-x=2-1
-x=1 /:(-1)
x=-1
g)
x=1-3(x+1)
x=1-3x-3
x+3x=-2
4x=-2 /:4
x=-1/2
h)
(x+1)-(x-1)=1
x+1-x+1=1
0=1-2
0=-1 - równanie sprzeczne
i)
1/2(x-1)=4
1/2x-1/2=4
1/2x=4+1/2
1/2x=4 i 1/2 / :1/2
x=9
j)
-1/4(2+x)=3/4x
-1/2-1/4x=3/4x
-1/4x-3/4x=1/2
-x=1/2 /:(-1)
x=-1/2
2010-03-10T15:04:42+01:00
A)2x + 2 = 4
2x = 4 - 2
2x = 2 /:2
x = 1

b)4=2(x-1)
4 = 2x - 2
-2x = -2 - 4
-2x = -6 /:(-2)
x = 3

c)3(x-2)=x
3x - 6 = x
3x - x = 6
2x = 6 /:2
x = 3

d)3(2x+3)=x-1
6x + 9 = x - 1
6x - x = -1 - 9
5x = -10/:5
x = -2

e)4(x-1)=3(x+1)
4x - 4 = 3x + 3
4x - 3x = 3 + 4
x = 7

f)-(x-1)=2
-x + 1 = 2
-x = 3/:(-1)
x = -3

g)x=1-3(x+1)
x = 1 -3x -3
x + 3x = 1-3
4x = -2/:4
x = 0,5

h)(x+1)-(x-1)=1
x+1 -x +1 = 1
(sry ale tego nie umiem :D)

i)1/2(x-1)=4 /*2
2 * 1/2 (x-1) = 8
1x -1 = 8
x = 7

j)-1/4(2+x)=3/4x /*(-4)
-4 * -1/4 (2+x)= -4*3/4x
-1(2+x)=-3x
-3-x=-3x
-x+3x=3
2x=3 /:2
x=1,5